(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Make in India is an international marketing campaign slogan by the Prime Minister of India, Narendra Modi to attract businesses from all over the world to invest and manufacture in India. The campaign is focused to fulfill the objective of creating employment, implementing secondary and tertiary sector, boosting the national economy, transforming India into a self-reliant country and giving global recognition to the Indian economy. Make in India which is a recipe for PM Narendra Modi’s goal of making India the manufacturing hub of the world. The idea of using cheap labor to produce for the world is not new. Through this initiative the Government of India aims to put its rapidly growing workforce to productive use, realizing that the service sector may not be the sole driver of the economy contributing around 55-60 of GDP. In this research paper ’Make in India’ an attempt has been made to review the pros and cons of this concept and understand its impact on the Indian economy.